PERBEDAAN KUALITAS TIDUR PADA ORANG DEWASA YANG MENGIKUTI BELA DIRI AIKIDO DENGAN ORANG DEWASA YANG TIDAK MENGIKUTI BELA DIRI AIKIDO DI BALI - Fitrotul Imaniyah; I Made Niko Winaya; I Wayan Sugiritama (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACT The addition of age and the variation of physical activity of each individual will increase the stress affecting the quality of sleep so that research done to determine the quality of sleep in adults who participate aikido martial arts with adults who no participate aikido martial arts as physical activity that can reduce stress level. The cross sectional analytic study with the sample was adults who fulfilled the inclusion and exclusion criteria of 86 people in each group. Samples filling out the Pittsburgh Sleep Quality Index (PSQI) questionnaire and the results were tested with a fisher exact test. The results showed a significant difference between sleep quality in two groups (p <0.05). With the percentage of result that is group A has good sleep quality 82 people (95,3%) and bad 4 people (4,7%), group B have good sleep quality 59 people (68,6%) and bad 27 people (31, 4%). So the conclusion is that groups of adults who participate aikido martial arts have better sleep quality than adults who no participate aikido martial arts. Keywords: Adult, Stess, Sleep Quality, Aikido Martial Arts.